Ambulantní monitorování krevního tlaku, kvalita spánku a věrohodnost noční hypertenze - Genzor, Samuel; Kociánová, Eva; Stanke, Ladislav; Štýbnar, Michal; Mizera, Jan; Vykopal, Martin (Cor et Vasa, 2024)
Nocturnal hypertension is a significant risk factor for cardiovascular mortality and morbidity. Its determination requires the use of 24-hour blood pressure monitoring (ABPM). However, the examination results can be less reliable in patients with insomnia, habitual short sleep or other sleep disorders. In these patients, it is possible to detect falsely high values of blood pressure in the night interval. At the same time, the treatment of sleep disorders itself could adjust the nighttime values of blood pressure and thus prevent unreasonably intensive treatment of high blood pressure. The article summarizes current knowledge about the effect of sleep quality on the accuracy of diagnosis using ABMP. At the same time, we present the study "How to diagnose true nocturnal hypertension?", which will analyze this clinical problem.
Keywords: kvalita spánku; Hypertension; Sleep Wake Disorders; Humans; Diabetes Complications; lidé; poruchy spánku a bdění; Sleep Quality; Blood Pressure Monitoring, Ambulatory; komplikace diabetu; klinická studie jako téma; ambulantní monitorování krevního tlaku; Clinical Studies as Topic; hypertenze